2020
DOI: 10.2147/idr.s273946
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Features and Co-Infections in Invasive Pulmonary Aspergillosis in Elderly Patients</p>

Abstract: Introduction: Invasive pulmonary aspergillosis (IPA) is a potentially lethal opportunistic infection. Old age is one of the important risk factors of IPA. However, data regarding the clinical characteristics and prognostic factors of elderly patients with IPA are limited, with data regarding co-infection of other bacteria or fungi even scarcer. Methods: We performed a retrospective study of elderly patients (aged≥60) with IPA diagnosed in the First Affiliated Hospital of Sun Yat-sen University from January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The main research results are as follows: first, 27.4% patients died during the follow-up period, and comorbidities were more common among the patients who died. The all-cause mortality of patients with proven IPA in this study is similar to that reported in previous studies involving Chinese patients ( 7 , 8 ); second, chest CT showed that pulmonary consolidation and pleural effusion were more common in the non-survival group; third, advanced age (>60 years), increased CRP levels (>14.1 mg/L), undergoing chemotherapy, and presence of pleural effusion were risk factors for all-cause mortality in patients with proven IPA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main research results are as follows: first, 27.4% patients died during the follow-up period, and comorbidities were more common among the patients who died. The all-cause mortality of patients with proven IPA in this study is similar to that reported in previous studies involving Chinese patients ( 7 , 8 ); second, chest CT showed that pulmonary consolidation and pleural effusion were more common in the non-survival group; third, advanced age (>60 years), increased CRP levels (>14.1 mg/L), undergoing chemotherapy, and presence of pleural effusion were risk factors for all-cause mortality in patients with proven IPA.…”
Section: Discussionsupporting
confidence: 90%
“…Advanced age and chemotherapy are correlated with the impairment of immune function. Therefore, they are recognized risk factors for infectious diseases, including aspergillosis ( 7 , 11 , 18 – 20 ). In this study, we also found that advanced age and chemotherapy increased the overall mortality of patients with proven IPA (HR: 10.7, CI: 2.5–44.9, P < 0.001; HR: 9.5, CI: 2.7–32.9, P < 0.001; respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study showed that compared with P. aeruginosa infection alone, A. fumigatus and P. aeruginosa co-infection caused more rapid decline in patients with lung function and worsened clinical outcomes (28). Co-infection is closely associated with mortality (27).…”
Section: Co-infection With Aspergillosismentioning
confidence: 99%
“…A clue to co‐infection is that the proportion of pulmonary cavitation may be significantly higher in the co‐infection than in the fungal infection group. Lymphopenia could be an indicator for co‐infection in the elderly patients with IPA (27). Compared with a single pathogen infection, a differential immune response is mounted when patients are infected with multiple pathogens, and this may lead to different clinical outcomes.…”
Section: Co‐infection With Aspergillosismentioning
confidence: 99%
“…IFDs caused by primary and opportunistic pathogens are identified among older individuals with immunosenescence 13 . Age is a significant predisposing factor for the development of fungal infection and is associated with increased mortality [14][15][16][17][18] . Comorbidities, increased use of corticosteroids and immunosuppressants, drug-drug interactions (DDIs) associated with polypharmacy,…”
mentioning
confidence: 99%